2016
DOI: 10.1007/978-3-319-39126-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Biosynthesis in Daucus carota

Abstract: Carrot (Daucus carota) is one of the most important vegetable cultivated worldwide and the main source of dietary provitamin A. Contrary to other plants, almost all carrot varieties accumulate massive amounts of carotenoids in the root, resulting in a wide variety of colors, including those with purple, yellow, white, red and orange roots. During the first weeks of development the root, grown in darkness, is thin and pale and devoid of carotenoids. At the second month, the thickening of the root and the accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…This post-transcriptional effect may be why Or has not been identified in previous carrot studies that have looked at carotenoid accumulation mechanisms at the transcription level (Simpson et al 2016). Mutations in the Or gene are associated with increased chromoplast formation, thereby providing more storage capability for carotenoids (Yuan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This post-transcriptional effect may be why Or has not been identified in previous carrot studies that have looked at carotenoid accumulation mechanisms at the transcription level (Simpson et al 2016). Mutations in the Or gene are associated with increased chromoplast formation, thereby providing more storage capability for carotenoids (Yuan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Two carrot paralog PSY genes are expressed differentially in leaves and roots during plant development ( Fuentes et al , 2012 ; Simpson et al , 2016 ), with DcPSY1 being mostly expressed in leaves and DcPSY2 in the storage root. Interestingly, although they share 68.34% identity at the amino acidic level, DcPSY1 is more closely related to PSYs of monocot species whereas DcPSY2 is most closely related to those of dicots ( Qin et al , 2011 ), providing evolutionary support for the putative differential role of these genes in carotenoid synthesis in carrot.…”
Section: Discussionmentioning
confidence: 99%
“…In the research of Nicolle et al, potassium was found to be the most abundant mineral in carrots 6 . Among these minerals, the content of iron, sodium and magnesium is highly dependent on the carrot variety, whereas the content of potassium and calcium is not 187 . In addition, carrot roots are a good source of vitamin E and ascorbic acid.…”
Section: Nutritionmentioning
confidence: 99%